Efektifitas Media Big Book dalam Meningkatkan Kemampuan Membaca Permulaan bagi Anak Berkesulitan Belajar Kelas II SDN 05 Kapalo Koto - Sisviona, Tika; Sopandi, Asep Ahmad (Jurnal Penelitian Pendidikan Khusus, 2021)
This research is motivated by the problems that in the field, namely a child with learning difficukties at SDN 05 Kapalo Koto who has difficulty in the field of reading, namely reading beginnings such as reading words even though they have previously been taught using direct media. Based on this, this study aims to prove the effectiveness of using Big Book learning media to improve beginning reading skills for children with learning difficulties in grade II SDN 05 Kapalo Koto. This research is an experimental research in the form of single subject research (SSR) with an A-B-A research design. The research subject is a child with learning disabilities. Data collection techniques are in the form of action tools using direct observation. Data were analyzed using graphic visual data analysis techniques. Based on the result of the analysis under conditions and between conditions, it was ststed that the initial reading ability, namely reading words, increased positively after being given an intervention using Big Book learning media.